Phytochemical Investigation of the Stem of Cassia tora Linn - Rai, K.N.; Kumari, Sarita (Asian Journal of Chemistry, 2010)
The isolation and characterization of a rare anthraquinone, 1-hydroxy-5-methoxy-2-methyl anthraquinone and its glycoside, 5-methoxy-2-methyl anthraquinone-1-O-α-L-rhamnoside (1) along with chrysophanol, emodin and <$Ebeta>-sitosterol from the stem of Cassia tora Linn. is reported.